(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This research paper discusses how George Saunders’ short tale “Isabelle” explores the brutalising impacts of racism in modern American culture as well as emotional anguish. The narrative shows Split Lip’s love and concern for his daughter Isabelle, who has special needs.